2018
DOI: 10.1002/jsde.12039
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Polypropylene Oxide Number on the Surface Properties of a Type of Extended Surfactant

Abstract: The surface properties of 5 extended surfactant C12–14P mE2S solutions in pure water and 0.1 M NaCl were investigated through surface tension and electrical conductivity measurements. The surface properties measured include the critical micelle concentration (CMC), critical surface tension (γcmc), maximum surface excess concentration (Γmax), minimum area occupied per surfactant molecule (Amin), and efficiency in surface tension reduction (pC20). The CMC values of the 5 surfactants decreased with increasing pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…It can be seen from Table data that the introduction of a few PO units considerably decreases the CMC, and increases the adsorption area per molecule, (in part because of the methyl branching of PO) and increases the surfactant tail length. Other recent studies confirmed these data (Lv et al, ).…”
Section: Physicochemical Properties Of Extended Surfactantssupporting
confidence: 73%
See 2 more Smart Citations
“…It can be seen from Table data that the introduction of a few PO units considerably decreases the CMC, and increases the adsorption area per molecule, (in part because of the methyl branching of PO) and increases the surfactant tail length. Other recent studies confirmed these data (Lv et al, ).…”
Section: Physicochemical Properties Of Extended Surfactantssupporting
confidence: 73%
“…This CMC phenomenon was found to also happen with the extended surfactants too, and to vary, not only with the tail, but also with different PON intermediates and head groups. (Charoensaeng et al, ; Fernandez et al, , b; Forgiarini et al, ; Goethals et al, ; Klaus et al, ; Lv et al, ; Miñana‐Pérez, ; Scorzza et al, , b; Witthayapanyanon et al, ).…”
Section: Physicochemical Properties Of Extended Surfactantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CMC is the concentration of surfactants in a solution above which micelles form. As shown in Table 2, the addition of extension (PO or EO) units into a surfactant molecule generally decreases the CMC (He et al, 2014;Liu et al, 2016a, b;Lv et al, 2018). For instance, Liu et al (2016a, b) have observed a decrease in CMC from 8.2 mmol.L À1 for the conventional SDS (C 12 -Sulfate) to 0.42 mmol.L À1 for C 12 -PO 4 -Sulfate (addition of 4 PO units) and down to 0.043 for C 12 -PO 12 -Sulfate (addition of 12 PO units).…”
Section: Critical Micelle Concentration (Cmc)mentioning
confidence: 94%
“…Beyond that point, structural variations such as the addition of an extension structure into a surfactant molecule impact its surface properties. In particular, this modifies molecular interactions at the interface, and thus affects the two main Lv et al (2018).…”
Section: Surface Properties and Micellizationmentioning
confidence: 99%